Nonlinear buckling and post-buckling analysis of imperfect cylindrical shells subjected to axial compressive load - Narayana, Y. Venkata; Gunda, Jagadish Babu; Reddy, P. Ravinder; Markandeya, R. (Journal of Structural Engineering, 2025)
Imperfection sensitivity of cylindrical shells subjected to axial compressive load is investigated by means of nonlinear buckling analysis and post-buckling analysis. Nonlinear buckling analysis involves the determination of the equilibrium path (or load-deflection curve) upto the limit point load by using the Newton-Raphson approach, whereas post-buckling analysis involves the determination of the equilibrium path beyond the limit point and upto the collapse load by using the arc-length approach. Limit point loads evaluated from these two approaches for various imperfection magnitudes show an excellent agreement, which clearly confirms the numerical results obtained. Finally, the influence of L/D and R/t ratios on post-buckling behavior of isotropic and composite cylindrical shells is briefly highlighted.